RELATIONSHIP BETWEEN EDUCATION LEVEL AND KNOWLEDGE OF DENTAL CARIES AND TOOTH BRUSHING SKILLS IN PREGNANT WOMEN IN SOUTH DENPASAR DISTRICT 2021 - I Gede Surya Kencana (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2021)
Dental and oral health is a healthy condition of the hard and soft tissues of the teeth and related elements in the oral cavity that allow individuals to eat, talk and interact socially without dysfunction, esthetic disturbances, and discomfort due to disease, occlusion irregularities and tooth loss so able to live productively socially and economically. The main problems of dental and oral health that are most commonly found in the community are dental caries and periodontal disease. One of the causes of dental caries is the behavior when brushing teeth is wrong because it is done in the morning shower and evening shower and not after breakfast and before bed at night. The purpose of this study was to describe knowledge about dental caries and tooth brushing skills in pregnant women in South Denpasar sub- district in 2021. This study used 40 pregnant women as respondents. The results of this study indicated that the knowledge of pregnant women about dental caries was mostly in the sufficient category, namely 19 people (47.50%). The average knowledge about dental caries in pregnant women was 73.75 with sufficient category. The majority of pregnant women brushing skills in the category of needing guidance were 17 people (42.50%). The average tooth brushing skill among pregnant women was 59.25 with the category of needing guidance. The results of this research on brushing skills based on knowledge of dental caries were that seven pregnant women (36.84%) had the skills to brush their teeth in the category of need guidance with sufficient knowledge of caries category. The Conclusion There is a relationship between education level and knowledge about dental caries in pregnant women and there is a relationship between knowledge level and tooth brushing skills in pregnant women in South Denpasar District.